Development of Interactive Learning Media Based on Problem-Based Learning: Improving Geography Learning Outcomes - Diki Audina; Abdul Hamid K; R Mursid (RIRAI Publisher, 2024)
The aim of this research is to produce interactive learning media based on a problem-based learning model that is feasible, practical, and effective in improving student learning outcomes in geography subjects. The ADDIE development model was the type of research used. The results of the research show: the material validation test obtained a score of 98% in the very feasible category, the media validation test obtained a score of 94% in the very feasible category, the design validation test obtained a score of 100% in the very feasible category, the individual and small group trials obtained a score of 86% in the very feasible category. , and the field trial obtained a score of 91% in the very worthy category, with an overall average result from the respondent category of 93%. The use of PBL-based interactive learning media in the experimental class obtained an average learning outcome of 84.17, while in the control class, which used video media and printed books, it obtained an average learning outcome of 79.50. The research data was declared normal and homogeneous. The results of the independent samples t test show tcount = 2.38 and ttable = 2.00 with a significance level of α = 0.05, so tcount > ttable. It can be interpreted that H0 is rejected and H1 is accepted, which means that the PBL-based interactive learning media product developed is effective. Furthermore, based on the results of the N-Gain calculation, a score of 60.78% was obtained, so this PBL-based interactive learning medium is classified as